English as a lingua franca in Colombia: insights from an emerging field - Mosquera Pérez, Jhon Eduardo (Árboles y Rizomas, 2025)
English as a Lingua Franca (ELF) is a field that has steadily gained traction around the world, and Colombia is no exception to this growing interest. Although there is still a relatively limited number of initiatives centered explicitly on ELF in English Language Teaching (ELT), researchers in the country are approaching the topic in diverse and enriching ways. In this article, I, an English teacher educator, non-native speaker, and researcher engaged with ELF, explore how Colombian scholars have been appropriating and engaging with ELF. By analyzing both empirical and conceptual initiatives that address not only ELF but also related notions such as World Englishes (WE), Global Englishes (GE), and even Global English Language Teaching (GET), I aim to illustrate how the field is gradually expanding within the territory. Rather than offering a superficial overview of ELF’s growth in Colombia, this critical reflective piece seeks to share with the national and international ELT academic community the multiple ways in which ELF can be meaningfully addressed. In doing so, it invites broader dialogues aimed at moving away from long-standing Anglo-centric dynamics that have shaped the field for too long.
Keywords: appropriation of English as a Lingua Franca; Colombia; English education; initial English teacher education